KARTU BERGAMBAR SEBAGAI MEDIA PEMBELAJARAN AKTIF SISWA KELAS I DI MADRASAH IBTIDAIYAH IZZUL ISLAM - Laila Ripani; Firdaus Ainul Yaqin; Farich Purwantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the application of picture cards as a medium for active learning and to identify the supporting and inhibiting factors at Madrasah Ibtidaiyah (MI) Izzul Islam. Using a qualitative descriptive approach, the research focuses on the learning process, student participation, and changes in motivation. Data were collected through observation and evaluated across two cycles. The results showed a significant increase in student activity, rising from 35% in the initial conditions to 90% in the second cycle. Furthermore, classical completeness improved from 40% to 95%, with the class average rising from 62.5 to 86.5. The findings indicate that picture cards effectively bridge abstract concepts into concrete visuals, which is suitable for the cognitive development of first-grade students. In conclusion, picture cards serve as an economical, flexible, and practical solution to enhance active learning and student learning outcomes.